Implementasi Pendidikan Ibadah dalam Program Didikan Subuh Taman Pendidikan Alquran (TPA) - Wenny Sulistiani; Murniyetti Murniyetti (An-Nuha, 2022)
The implementation of Islamic religious education is important to be given to children from an early age, not only in formal or informal education, worshipping education can also be obtained from non-formal education. One of which is in the activities of the Al-Qur'an Education Park (TPA), namely the fajr education program. This study aimed to find out how the implementation of worshipping education in the fajr education program of the Baitussalam Mosque's Al-Qur'an Education Park (TPA). This study used a qualitative method with the type of case study research. The sources of data were taken from five informants from the Baitussalam Mosque Al-Qur'an Education Park (TPA), namely the headmaster and four teachers through in-depth interviews using the purposive sampling technique. Overall, the conclusion of the research showed that the implementation of the fajr education activities is divided into three parts; preliminary activities, core activities, and closing activities. Preliminary activities begin with reading shalawat, absent the fajr prayer in congregation, checking the presence of the fajr education operator, then submitting it to the protocol. The core activities are contained in the Baitussalam Mosque's Fajr Educational Program for the Al-Qur'an Education Park (TPA), namely memorizing readipracticingtice, and delivering material by the teacher. The closing activity begins with the announcement of the group with the numerous Fajr prayers, the numerous infaq groups, the best group of the day, giving prizes to the group with the plentiful points, then ends with reading the closing prayer of the assembly and praying out of the mosque.